2020
DOI: 10.1021/acsbiomaterials.0c00492
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Nanocellulose and Titania Hybrids: Cytocompatible and Cryopreservable Cell Carriers

Abstract: Carrier-assisted cell transplantation offers new strategies to improve the clinical outcomes of cellular therapies. Bacterial nanocellulose (BC) is an emerging biopolymer that might be of great value in the development of animal-free, customizable and temperature-stable novel cell carriers. Moreover, BC exhibits a myriad of modification possibilities to incorporate additional functionalities. Here, we have synthesized BC-titanium dioxide (TiO2) nanocomposites (BC/TiO2) to evaluate and compare the suitability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…There are a few examples in the literature about the usage of BNC supports in stem cell culture that do not report on the need for coating BNC with ECM proteins to provide cell adhesion moieties. [48][49][50] Similarly, in our previous work with human dermal fibroblasts, [22] we found that BNC coating was not required to facilitate cell attachment. However, the here presented results prove that the plasma-assisted ECM protein functionalization is crucial for hESC-LSC attachment and survival on the BNC substrates.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…There are a few examples in the literature about the usage of BNC supports in stem cell culture that do not report on the need for coating BNC with ECM proteins to provide cell adhesion moieties. [48][49][50] Similarly, in our previous work with human dermal fibroblasts, [22] we found that BNC coating was not required to facilitate cell attachment. However, the here presented results prove that the plasma-assisted ECM protein functionalization is crucial for hESC-LSC attachment and survival on the BNC substrates.…”
Section: Discussionsupporting
confidence: 78%
“…[62,70] Moreover, the thermal stability of BNC enables both its sterilization by heat and cryopreservation. [22] The latest being of particular significance because it makes the cryobanking of ready-to-use hESC-LSC/BNC constructs a feasible possibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 We have recently validated BNC in diverse biological scenarios providing data on its cytocompatibility, lack of endotoxins (0.04 ± 0.01 Endotoxin Units per mL) after its biosynthesis as well as suturability and manageability in preclinical settings. 37,39 These findings, combined with the appealing mechanical properties reported here, positioned BNC as a suitable candidate for soft tissue repair patches and therefore in vivo studies were conducted. The anti-adhesion behaviour, biocompatibility and tissue integration characteristics of the BNC patches have been evaluated with a pilot animal study.…”
Section: Discussionmentioning
confidence: 83%